Biotransformation of ginsenosides F4 and Rg6 in zebrafish. Issue 7 (3rd July 2018) - Shen, Wen-Wen; Zhang, Hai-Xia; Qiu, Shou-Bei; Wei, Ying-Jie; Zhu, Fen-Xia; Wang, Jing; Wang, Dan-Dan; Jia, Xiao-Bin; Tang, Dao-Quan; Chen, Bin
Abstract: Ginsenosides F4 and Rg6 (GF4 and GRg6 ), two main active components of steamed notoginseng or red ginseng, are dehydrated disaccharide saponins. In this work, biotransformation of ginsenosides F4 and Rg6 in zebrafish was investigated by qualitatively identifying their metabolites and then proposing their possible metabolic pathways. The prediction of possible metabolism of ginsenosides F4 and Rg6 using zebrafish model which can effectively simulate existing mammals model was early and quickly performed. Metabolites of ginsenosides F4 and Rg6 after exposing to zebrafish for 24 h were identified by Ultraperformance Liquid Chromatography/Quadrupole-Time-of-Flight Mass Spectrometry. A total of 8 and 6 metabolites of ginsenosides F4 and Rg6 were identified in zebrafish, respectively. Of these, 7 and 5, including M1, M3−M5, M7−M9 and N1 (N5), N2, N4 (N9), N7−N8 were reported for the first time as far as we know. The mechanisms of their biotransformation involved were further deduced to be desugarization, glucuronidation, sulfation, dehydroxylation, loss of C-17 and/or C-23 residue pathways. It was concluded that loss of rhamnose at position C-6 and glucuronidation at position C-3 in zebrafish were considered as the main physiologic and metabolic processes of ginsenosides F4 and ginsenosides Rg6, respectively.